Rethinking NUTS 2 Regions in Turkey with Logistic Firms' Distribution Systems - Sakarya, Adem; Erkut, Gulden; Evren, Yigit (KARE PUBL, 2015)
The Nomenclature of Territorial Units for Statistics (NUTS) system of Turkey has received various criticisms since it was established some 15 years ago as part of Turkey's application to join the EU. The aim of the present paper was to compare Turkey's NUTS 2 statistical regions with the distribution systems of local third-party logistics firms. Correlation analysis was employed to measure the degree of association between two variables: the surface area of NUTS 2 regions and their population. Ranges in which services are provided were used to evaluate the logistics firms' distribution systems. According to the results, while a positive relationship between the two variables was determined in the logistics sector, the same did not hold true for the NUTS 2 system.
Keywords: 3PL; NUTS2; urban hierarchy; logistic; correlation; Public Administration